EU General Data Protection Regulation (GDPR) – An implementation and compliance guide, fourth edition - Team, IT Governance Privacy (IT Governance Publishing Ltd, 2020)
Understand your GDPR obligations and prioritise the steps you need to take to comply The GDPR gives individuals significant rights over how their personal information is collected and processed, and places a range of obligations on organisations to be more accountable for data protection. The Regulation applies to all data controllers and processors that handle EU residents' personal information. It supersedes the 1995 EU Data Protection Directive and all EU member states' national laws that are based on it - including the UK's DPA (Data Protection Act) 1998. Failure to comply with the Regulation could result in fines of up to i20 million or 4% of annual global turnover - whichever is greater. This guide is a perfect companion for anyone managing a GDPR compliance project. It provides a detailed commentary on the Regulation, explains the changes you need to make to your data protection and information security regimes, and tells you exactly what you need to do to avoid severe financial penalties. Clear and comprehensive guidance to simplify your GDPR compliance project Now in its fourth edition, EU General Data Protection Regulation (GDPR) - An implementation and compliance guide provides clear and comprehensive guidance on the GDPR. It explains the Regulation and sets out the obligations of data processors and controllers in terms you can understand. Topics covered include: The DPO (data protection officer) role, including whether you need one and what they should do; Risk management and DPIAs (data protection impact assessments), including how, when and why to conduct one; Data subjects' rights, including consent and the withdrawal of consent, DSARs (data subject access requests) and how to handle them, and data controllers and processors' obligations; Managing personal data internationally, including updated guidance following the Schrems II ruling; How to adjust your data protection processes to comply with the GDPR, and the best way of demonstrating that compliance; and A full index of the Regulation to help you find the articles and stipulations relevant to your organisation. About the authors The IT Governance Privacy Team, led by Alan Calder, has substantial experience in privacy, data protection, compliance and information security. This practical experience, their understanding of the background and drivers for the GDPR, and the input of expert consultants and trainers are combined in this must-have guide to GDPR compliance. Start your compliance journey now and buy this book today.